NALAR KRITIS HUKUM ISLAM TERHADAP RESPON MODERNITAS - Edy Imam Supneo; Ansari Ansari (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
Islamic law will still be able to respond to new issues arising, as a consequence of the advancement of science and technology. In the Treasures of Islamic Sciences, Fiqh (Islamic law) is one of the classical disciplines that are always loaded with interesting discourse, the natural character of the Islamic law as part of the Islamic Shari'a and permanent (qath'i) and must be received